Neonatal cholestasis as the onset symptom of McCune–Albright syndrome: case reports and a literature review - Fang, Weiyuan; Zhang, Yanhui; Chen, Lian; Xie, Xinbao (Frontiers in Pediatrics, 2023)
MAS can be one of the causes of neonatal cholestasis, which may be its first manifestation. Extrahepatic coexisting symptoms of MAS and liver histology can help to distinguish MAS from other etiology of cholestasis. Detection of GNAS mutations in liver tissue may shorten diagnostic time and is of particular interest in the partial and atypical forms of MAS with neonatal cholestasis. Neonatal cholestasis in children with MAS can self-resolve, but the liver dysfunction persists and malignant lesion exists.